Study of antimicrobial susceptibility to respiratory pathogens in pigs - Neverkovets, N. Yu.; Неверковець, Н. Ю.; Chumak, Vladislav; Chumak, V.; Chumak, V. O.; Chumak, V. A.; Chumak, Vladyslav; Чумак, Владислав Олександрович; Kokariev, A. V.; Kokariev, A.; Kokariev, Andrii; Kokarev, A. V.; et al. (Дніпровський ДАЕУ, 2025)
The antimicrobial susceptibility of common respiratory pathogens of pigs including Actinobacillus (Haemophilus) pleuropneumoniae, Pasteurella multocida, Streptococcus suis, and Trueperella (Arcanobacterium) pyogenes – was studied in the samples isolated from industrial pig farms located in east and central province of Ukraine. The study was carried out with analysis the results of surveillance the microbial strains susceptibility in the 620 animals with signs of respiratory pathology. The samples were isolated and tested during 2023-2024 at the Research Center for Biosafety and Environmental Control of Agricultural and Industrial Complex Resources. To determine the sensitivity of bacteria to antibiotics, the Kirby-Bauer agar diffusion method was used. Resistance was determined against to particular antibiotic groups, the application of which is regulated by the government requirements of Ukraine. In order to identify differences in the prevalence of resistant strains to individual antibiotics dependent on the year of the study, the results were statistically analyzed with using the χ 2 criterion. The dynamics of the spread of resistance to individual antimicrobial drugs were identified. The most effective category D drugs that are allowed to be used for the treatment of animals on the first day of infection caused by the studied bacteria are drugs containing Amoxicillin. However, resistance to Amoxicillin in A. pleuropneumoniae isolates increased from 12% in 2023 to 18% in 2024. The consequence of the requirements breach for the rational use of antimicrobial drugs was the resistance generation in respect to category B antimicrobial drugs, which are allowed to be used for the treatment of productive animals only in the absence of effective drugs of categories C or D. Fluoroquinoloneresistant strains of S. suis were detected in 6%, and A. pleuropneumoniae in 9-18% of samples, respectively in 2024. Among the studied isolates of P. multocida and T. pyogenes, there is no observed the resistance against fluoroquinolones. The introduction of regular monitoring of antibiotic resistance will allow selecting the most effective antimicrobial treatment regimen for respiratory pathology in pigs and will contribute to the implementation of the requirements of the “One Health” concept in respect with agricultural production. Досліджено чутливість до протимікробних засобів поширених респіраторних патогенів свиней - Actinobacillus (Haemophilus) pleuropneumoniae, Pasteurella multocida, Streptococcus suis, Trueperella (Arcanobacterium) pyogenes. Робота виконана на ізолятах, одержаних від 620 тварин із ознаками респіраторної патології, які надходили протягом 2023-2024 років до Науково-дослідного центру біобезпеки та екологічного контролю ресурсів АПК. Для визначення чутливості бактерій до антибіотиків використовували метод дифузії в агар за Kirby-Bauer. Стійкість визначали до антибіотиків, використання окремих категорій яких регламентує в Україні “Порядок використання протимікробних ветеринарних лікарських засобів у ветеринарній медицині”. З метою виявлення відмінностей у поширеності резистентних штамів до окремих антибіотиків залежно від року дослідження результати оброблено статистично з розрахунком критерію χ2. Виявлено динаміку поширення резистентності до окремих протимікробних препаратів. Найбільш ефективними препаратами категорії Д, які дозволено використовувати для лікування тварин у перший день інфекції, викликаної досліджуваними бактеріями є препарати з Амоксициліном. Проте резистентність до Амоксициліну у ізолятів A. pleuropneumoniae зросла із 12% у 2023 році до 18% у 2024 році. Наслідком порушення вимог щодо раціонального використання протимікробних препаратів є поява резистентності до протимікробних препаратів категорії В, які дозволено використовувати для лікування продуктивних тварин лише за відсутності ефективних препаратів категорій C або Д. У 2024 році стійких до фторхінолонів штамів S. suis виявлено 6%, а A. pleuropneumoniae у 9-18% зразків відповідно. Серед досліджених ізолятів P. multocida і T. pyogenes резистентність до фторхінолонів відсутня. Впровадження регулярного моніторингу антибіотикорезистентності дозволить підбирати найбільш ефективну схему протимікробного лікування респіраторної патології свиней та сприятиме втіленню вимог концепції “Єдине здоров’я” у агровиробництво.
Дослідження чутливості до антимікробних речовин збудників респіраторних захворювань свиней
Чумак Владислав Олександрович https://orcid.org/0000-0002-0140-3982 Кокарєв Андрій Вікторович https://orcid.org/0000-0002-5673-5984
Keywords: antibiotic resistance; антибіотикорезистентність; disk diffusion; дискова дифузія; monitoring; моніторинг